How the Department of Youth and Sports Does Job Analysis - Erwin Erwin; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The method by which the Kemenpora Department of Youth and Sports conducts job analyses is the focus of this research. Due to a lack of specificity on the duties expected of the Department, the findings demonstrate that the present job analysis is inadequate. The guidelines of Permenpan RB No. 1 of 2020 are not followed, and it becomes difficult to map out responsibilities. The data is primarily gathered by an internal staff using templated approaches, which raises concerns regarding its validity and dependability. The job analyst, the person actually performing the work, and the person in charge of the job are the three key people who provide information for job analyses. There is a lack of understanding between jobholders and their managers regarding organizational strategy and job tasks. Additionally, job analysts are not very competent in their roles. Additionally, the study found that due to a lack of checks and balances, the data is not accurate or dependable. We propose a four-stage job analysis paradigm to address this issue. Planning, data collection, data treatment, and result sharing are all parts of this approach. The objective is to improve the thoroughness and accuracy of job analyses.